A Survey of Medium Access Mechanisms for Providing Robust Audio Video Streaming in IEEE 802.11aa Standard - Hassan Ibrahim Zawia; Rosilah Hassan; Dahlila Putri Dahnil (IEEE Access, 2018)
The amendment of medium access control (MAC) in 802.11 has been published as the 802.11aa standard. The new standard enhances the quality of service (QoS) provisioning for robust audio-video (AV) streaming in wireless local area networks (WLANs). The 802.11aa standard is mainly an extension of the 802.11e, 802.11n, and 802.11v standards. In this survey, we describe the mechanisms of Medium Access Control (MAC) in 802.11aa in greater detail. The interworkings of the different network technologies of Quality of Service (QoS) WLAN and Ethernet are explained. We add mechanisms from the 802.1Q standard to complement 802.11aa regarding the stream reservation protocol and strict priority algorithm to provide a complete vision of the standard. Research challenges include incorporating a wide range of mechanisms in the 802.1Q wireline standard in the 802.11aa wireless standard. To enhance the interworking of the 802.1Q and 802.11aa standards, we propose to unify three mechanisms: the maps Access Categories (ACs), the transmit access queues, and transmission selection algorithm. This survey provides necessary guidelines for researchers and designers to implement future Wireless Local Area Network (WLAN) 802.11aa with an emphasis on the requirements for robust Audio-Video (AV) streaming.